Symposium "Trio for the preservation of joint health" (with the support of "Heel RUS" LLC) - article Editorial (Современная ревматология, 2024)
On September 7, 2024, as part of the scientific program of the VII Eurasian Congress of Rheumatologists in Kyrgyzstan, a symposium "Trio for the preservation of joint health" was held with the support of "Heel RUS" LLC, at which doctors from Russia, Kyrgyzstan, Uzbekistan, Kazakhstan and other countries discussed modern views on the diagnosis and treatment of osteoarthritis (OA). Rehabilitation techniques for OA were also presented.